Aquatic Coleoptera and Heteroptera inhabiting waterbodies from Berisso (Buenos Aires province, Argentina) - Fernandez, Liliana Alicia (2006)
Coleoptera and Heteroptera associated with aquatic environments were studied at Berisso, near Río de La Plata estuary (Buenos Aires Province, Argentina). Four waterbodies were characterized and compared: artificial pond, shallow pool, stream and artificial channel. Sampling was done twice a month, with a round sieve, for 12 months (April 1999 to April 2000). Sampling was quantified using a discrete unit of time (one hour/worker). Where floating vegetation was present, four 25 cm diameter samples were extracted and placed in a Berlese-Tullgren funnel for 48 hours. Temperature, pH and conductivity were measured. Specimens were preserved in 70° ethanol. Similarities in taxonomic composition among sampling stations were quantified using Jaccard’s index based on a presence/absence matrix for the insect fauna of each sampling station. A total of 68 species belonging to 8 families of Coleoptera and 11 families of Heteroptera were collected. The highest number of species (41) was recorded in the shallow pool (stream 34 species; artificial pond 29; artificial channel 25). The highest specific diversity values were observed during spring in all sampling stations. The highest frequency of Coleoptera was shown by Helochares talarum Fernández and Suphisellus nigrinus (Aubé) (?). In the Heteroptera it was shown by Lipostemmata humeralis Berg, Lipogomphus lacuniferus Berg and Rheumatobates bonariensis (Berg). The most abundant species were not necessarily the most frequent ones. Coleoptera is the most important group in species richness. Each environment had a taxocoenosis of Coleoptera and Heteroptera with inherent characteristics.